The Online National Intervener Training Pilot Project. (July 2022) - Probst, Kristi M.; Morgan, Sam
Introduction: Interveners are paraeducators who have been trained in deafblind strategies. This study evaluated the effectiveness of an online training project for intervener candidates.Methods: The training project utilized the Open Hands, Open Access (OHOA) Intervener Training Modules in conjunction with synchronous meetings and coaching.Results: Upon completion of the program, a survey was conducted to evaluate the participant's preparation to perform their job as an intervener, the most helpful parts of the program, suggestions for improvement, and overall satisfaction with the training. Additionally, participant attrition (17%) and pursual of intervener certification were examined.Discussion: The results of this study indicated that this type of program can successfully impart the knowledge and skills one needs to improve their skills as an intervener, reduce attrition of participants, and individuals can subsequently complete a rigorous certification process based on national standards.Implications for Practitioners: State deaf-blind projects as well as other entities engaged in professional development can use the materials from this project to train staff in deafblind strategies. The flexibility built into this training can be enticing for educators and paraeducators seeking professional development.